Job Autonomy, Organizational Culture, and Employee Creativity as Predictors of Innovative Work Behavior: The Mediating Role of Knowledge Sharing at Bank Indonesia - Yulianatasia Simanjuntak; Lailla, Nor (Universitas Muhammadiyah Pontianak, 2026)
This study examines the determinants of Innovation Work Behavior (IWB) among 150 employees of Bank Indonesia's Compliance Management and Reporting Department (DPKL), using PLS-SEM with Knowledge Sharing as a mediator. Employee Creativity and Knowledge Sharing significantly predict IWB, while Organizational Culture affects IWB indirectly through Knowledge Sharing. Job Autonomy shows no significant effect on either Knowledge Sharing or IWB, reflecting the constraints of a highly regulated environment. The model explains 80.2% of IWB variance. This study contributes by testing an integrated antecedent-mediator model in an underexplored central-bank compliance setting. Keywords: Job Autonomy; Organizational Culture; Employee Creativity; Knowledge Sharing; Innovation Work Behavior; PLS-SEM